HEPATIC TRANSPORTER PROTEIN EXPRESSION IN FETUSES, NEONATES AND YOUNG INFANTS. Issue 1 (14th December 2015) - Mooij, Miriam; de Steeg, Evita Van; Wortelboer, Heleen; Vaes, Wouter; Tibboel, Dick; Wildt, Saskia De
Abstract : Background: Transporters are membrane-bound proteins involved in trafficking substrates (e.g. drugs) across membranes of among others hepatocytes. Limited data exists on the developmental expression. We aim to study protein expression of transporters in fetal, neonatal and infantile liver. Methods: Transporter protein expression (ABCB1, ABCG2, ABCC2, ABCC3, BSEP, GLUT1, MCT1, OATP1B1, OATP2B1, OCTN2) was quantified using UPLC-MS-MS, on snap-frozen post mortem livers (Erasmus MC tissuebank) and adult control livers (UMC-Groningen). Protein expression was determined in isolated crude membrane and quantified using stable-isotope-labelled peptides. Age groups were compared with Mann-Whitney test and post hoc Bonferroni-correction (significance p <0.05). Data was compared to mRNA expression. Results: 25 liver samples were studied. 10 fetal [median gestational age 23.2 weeks (range 16.4–37.9)], 12 pediatric [postnatal age 1 week (0–11.4) and gestational age at birth 35.1 weeks (27.1–41.0)], and 3 adult liver samples. ABCB1, ABCC2, OATP1B1, OATP2B1 expressions appeared similar in fetuses, pediatrics and adults. MCT1 expression was similar in fetuses and adults, but higher in pediatrics. BSEP expression was lower in fetuses and pediatrics than in adults. ABCC3 expression was lower level in fetuses than in adults, but not in pediatrics compared to adults. ABCG2, GLUT1, OCTN2 expressions were higher in fetuses than in adults, but similar in pediatrics and adults. Conclusion: Hepatic transporters appear in different developmental expression profiles. ABCB1, ABCC2, OATP1B1 protein expression appears stable. This contrast previous mRNA expression data, which showed lower expression in fetus/neonate. The age-related differences in transporter expression may result in age-dependent pharmacokinetics of substrates.